2021
DOI: 10.3390/su131910922
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Environmental Impacts of Construction Projects in Time-Cost Trade-Off Project Scheduling Problems with CoCoSo Multi-Criteria Decision-Making Method

Abstract: Currently, construction projects have a significant share in environmental pollution. Usually, the employers and managers of construction projects pay attention to the project implementation with the shortest duration and the lowest cost, whereas less attention is paid to the environmental effects of the implementation of projects. Sustainable development requires the planning and implementation of construction projects, taking environmental impacts, along with other factors, into account. Few studies have inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Combining three evaluation score strategies to make the final decision results more reasonable and superior, which not only avoids the problem of biased results caused by a single decision method but also effectively integrates multiple aggregation ideas to achieve internal balance and thus weakens the variability of decision results. Now the CoCoSo method is widely used in different areas, such as blockchain platform selection (Lai et al, 2022), logistics center site selection (Ulutas et al, 2020;Banihashemi et al, 2021), supplier selection (Yazdani et al, 2019b;Lai et al, 2020;Wang C. N. et al, 2022;Wei et al, 2022) due to its high flexibility and simple calculation.…”
Section: Evaluation Process Based On Entropy-cocoso Frameworkmentioning
confidence: 99%
“…Combining three evaluation score strategies to make the final decision results more reasonable and superior, which not only avoids the problem of biased results caused by a single decision method but also effectively integrates multiple aggregation ideas to achieve internal balance and thus weakens the variability of decision results. Now the CoCoSo method is widely used in different areas, such as blockchain platform selection (Lai et al, 2022), logistics center site selection (Ulutas et al, 2020;Banihashemi et al, 2021), supplier selection (Yazdani et al, 2019b;Lai et al, 2020;Wang C. N. et al, 2022;Wei et al, 2022) due to its high flexibility and simple calculation.…”
Section: Evaluation Process Based On Entropy-cocoso Frameworkmentioning
confidence: 99%
“…Recent research works have indicated that the conventional project iron triangle cannot meet all the prerequisites of project performance, because in today's complex projects, it is necessary to consider other performance criteria such as stakeholders' satisfaction, health, safety, and the environment [35]. Banihashemi et al (2021) considered environmental impacts in developing project schedules [36]. Additionally, Naghizadeh Vardin et al (2021) addressed the sustainability indicators for contractor selection in the construction industry [37].…”
Section: Performance Assessment Modelsmentioning
confidence: 99%
“…Huynh et al (2021) compared the performance of four metaheuristic algorithms in solving the TCQ trade-off problem considering carbon dioxide emission [29]. attempted to simultaneously minimize the project cost, time, and environmental effects [30]. Liu et al (2021) developed a model to deal with RCPSP taking consumable resources into account, and solved the proposed model by using the constraint programming (CP) method [31].…”
Section: Literature Reviewmentioning
confidence: 99%